Osteosarcopenia as a risk factor for depression: Longitudinal findings from the SHARE study - Nicola Veronese; Francesco Saverio Ragusa; Shaun Sabico; Ligia Juliana Dominguez; Mario Barbagallo; Gustavo Duque; Lee Smith; Nasser Al-Daghri (Bone Reports)
Background: Osteosarcopenia (i.e., the co-existence of osteoporosis and sarcopenia) and depression are highly prevalent among older people. However, the association between osteosarcopenia and depression in older people is largely unknown. Therefore, the present study aims to investigate this possible association in a representative sample of the older adult population in Europe and Israel. Methods: Osteosarcopenia was defined as the concomitant presence of osteoporosis and sarcopenia; depressive symptoms in the SHARE study were self-reported using the EURO-D scale. The association between the presence of osteosarcopenia at baseline in people free from depression and incident depression during 12 years of follow-up was analyzed using a Cox's regression analysis, adjusting for several baseline covariates. Results: 16,452 participants were included (mean age 63.7, SD 9.6; females 50.6 %). During the follow-up period, 5056 participants (31.1 % of the initial population) became depressed. People affected by osteosarcopenia became depressed in more than half of the cases compared to a quarter of controls. After adjusting for several potential baseline confounding variables, only sarcopenia (HR, hazard ratio = 1.17; 95 % CI, confidence intervals 1.04–1.32; p = 0.009) and osteosarcopenia (HR = 1.27; CI 95 % 1.12–1.58; p = 0.003) were significantly associated with a higher risk of depression. Limitations: Definition of sarcopenia using an anthropometric equation; definition of depression using the EURO-D scale. Conclusions: The present study identified a significant association between osteosarcopenia and depression over 12 years of follow-up, mainly driven by sarcopenia. If future research confirms the present findings, it may then be prudent to target those with osteosarcopenia to aid in the prevention of onset depression.